Peran Strategi Pengembangan Sumber Daya Manusia terhadap Peningkatan Kapasitas dan Kemandirian Anggota PKK di Era Digital:Studi PKK Dusun Sitirejo, Kecamatan Wagir, Kabupaten Malang - wiwit wiwit setyo wardani (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
This study aims to explore in depth how human resource development (HRD) strategies can enhance the capacity and independence of members of the Family Empowerment and Welfare Movement (PKK) in the digital era. The research was conducted in Sitirejo Hamlet, Wagir District, Malang Regency, involving 42 respondents consisting of both administrators and active members. A descriptive quantitative approach was applied, with data collected through questionnaires, interviews, and direct field observations to provide an authentic understanding of the organization’s real conditions. The findings reveal that digital-based training, improved technological literacy, and continuous mentoring not only strengthen members’ technical competencies but also foster confidence, motivation, and a spirit of collaborative learning among PKK participants. Through well-planned digital transformation initiatives, rural women have become more self-reliant, creative, and resilient in responding to social and economic challenges. This research highlights that adaptive and sustainable HRD strategies are vital foundations for building productive, independent, and competitive community organizations in the digital age.